Intrinsic PD‐L1 Degradation Induced by a Novel Self‐Assembling Hexapeptide for Enhanced Cancer Immunotherapy - Hongxia Zhang; Ming Ji; Yamei Wang; Mengmeng Jiang; Zongyu Lv; Gongyu Li; Lulu Wang; Zhen Zheng (Advanced Science)
Abstract Programmed death‐ligand 1 (PD‐L1) is a critical immune checkpoint protein that facilitates tumor immune evasion. While antibody‐based PD‐1/PD‐L1 inhibitors have shown promise, their limitations necessitate the development of alternative therapeutic strategies. This work addresses these challenges by developing a hexapeptide, KFM (Lys‐Phe‐Met‐Phe‐Met‐Lys), capable of both directly downregulating PD‐L1 and self‐assembling into a ROS‐responsive supramolecular hydrogel. This dual functionality allows Gel KFM to function as a localized drug delivery system and a PD‐L1 inhibitor. Loading the hydrogel with mitoxantrone (MTX) and metformin (MET) further enhances the therapeutic effect by combining chemotherapy with PD‐L1 downregulation. In vitro and in vivo studies demonstrate significant tumor growth inhibition, increased CD8+ T cell infiltration, and reduced intratumoral PD‐L1 expression following peritumoral administration. Mechanistically, KFM promotes PD‐L1 degradation via a ubiquitin‐dependent pathway. This “carrier‐free” delivery system expands the role of supramolecular hydrogels beyond passive carriers to active immunotherapeutic agents, offering a promising new strategy for cancer therapy.